The Content Analysis of Cognitive and Psychomotor Domains in an English Textbook for Senior High School Grade XI - Halla, Debi Maulana Ahsan; Rustandi, Andi (Journal of English Education Program (JEEP), 2024)
This research investigated the evaluation of an English textbook. This research aimed to analyze the relevance between the revised edition of the 2013 Curriculum English textbook “Modul Pembelajaran SMA Bahasa Inggris” for Senior High School grade XI to the Core Competence concerning cognitive and psychomotor domains. This research employed content analysis under descriptive qualitative as the research design. The data of this research was collected from the English textbook “Modul Pembelajaran SMA Bahasa Inggris” for Senior High School grade XI. The collected data was categorized into tables and elaborated into each core Competence, Learning Indicator, and Learning process. The data was analysed using a conclusion drawn and then it was interpreted. The results of this research indicated that the relevance between learning indicators to the Basic competencies is adequately relevant for the Cognitive Domain and slightly relevant for the Psychomotor Domain. Besides, the relevance between learning activity to the Basic competencies is barely relevant for the Cognitive Domain and barely relevant for the Psychomotor Domain. The findings came up with the fact that the English textbook has more emphasis on the cognitive domain than the psychomotor aspect. Thus, the teacher should cover the rest of those aspects in the process of teaching and learning so that the students can achieve the Basic competencies optimally.